A Study Probing the Subjective Theory of Secondary School Teachers in Greece - Αθανασάκη, Άννα; Φλουρής, Γεώργιος (Education Sciences, 2023)
The present study purports to delineate the subjective theory of secondary school teachers in Greece. This type of theory refers to the cognitive and psychological construct of knowledge, beliefs, attitudes, internalized images and cognitive schemas which are used to solve important issues and dilemmas during the teaching act. Despite the fact that the subjective theory directs teachers’ thinking and behavior it cannot be assessed only with academic criteria. Given the above context we conducted a quantitative study via the use of a questionnaire in order to ascertain the subjective theory of secondary school teachers of certain specializations. The analysis of the data reveals that there are significant factors that form teachers’ professional identity which transcend their initial training. The originality of the study lies with the fact that it delineates secondary teachers’ subjective theory and synthesizes an operational definition for this subject.